Proposição de indicadores de desempenho logístico a partir da análise do planejamento estratégico: estudo de caso de uma empresa de saneamento do Estado do Ceará - Lima, Maysa Rafaelle Silva de Agrela (2011)
Sanitation is an indispensable asset in the quest to guarantee the quality of life in society, and should be seen as a fundamental right. Among the tools used to ensure universalisation of basic sanitation, there is the logistics of acquisition, storage and distribution of parts and equipment used in the implementation and maintenance of water treatment and sewage, allowing possible expansion of these services according to the dynamics of population growth. The management of logistics activities in the sanitation companies is a sine qua non for ensuring the operational excellence of sanitation services, allowing the reduction of costs along with higher capacity and speed in providing these services. This paper presents a proposed set of indicators of logistics performance that seeks to provide key information for making decisions related to the efficiency of logistics processes of the Distribution Center of Water and Sewage Company of Ceara - CAGECE, sanitation company provider of utilities, water supply and sanitation in the state of Ceara. To get to this proposal it was presented all the stages of the strategic planning of CAGECE and its Logistics Management - GELOG, both based on the Balanced Scorecard. This work is extremely relevant, since it can help companies of sanitation in the implementation of the evaluation of logistics performance indicators, enabling the improvement of operational excellence of basic sanitation services disposed to the population.